1998
DOI: 10.1046/j.1469-7580.1998.19330323.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐generated three‐dimensional reconstructions of serially sectioned mouse embryos

Abstract: We have been involved with a group of computer scientists and anatomists in the development of computerbased methodologies that not only combine the advantages of scanning electron microscopy and conventional histology, but provide the additional dimension of tissue recognition. The latter is achieved by the appropriate labelling of tissues and structures by delineation or ' painting '. Individually segmented anatomically defined tissues can be highlighted in a particular colour and viewed either in is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Briefly, embryos were removed from pregnant C57BL/6J mice (CLEA Japan) and staged according to morphological criteria to confirm the gestational day (Kaufman et al, 1998). Developing mouse cerebral cortex was dissected from E14 embryos.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, embryos were removed from pregnant C57BL/6J mice (CLEA Japan) and staged according to morphological criteria to confirm the gestational day (Kaufman et al, 1998). Developing mouse cerebral cortex was dissected from E14 embryos.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Developing mouse cerebral cortex was dissected from embryos at E13.5 to E14.5. The precise gestational day was determined according to previously established morphological criteria (Kaufman et al, 1998). NPCs from each embryo were collected and cultured separately.…”
Section: Cortical Npc Culture and Differentiation Conditions In Gad Micementioning
confidence: 99%
“…S, saccule; OE, olfactory epithelium from serial sections has remained a diffi cult task. Kaufman et al 18 showed the topological relationship of organs and tissues in embryo. They categorized the images on sliced sections into several areas, and then reconstructed each area with the aid of a computer system.…”
Section: Described Reconstructed Human Bone By Micro-ctmentioning
confidence: 99%
“…Perturbation and transplantation experiments have lead to formation of extra bony entities in the face (Lee SH et al 2001;Helms and Schneider 2003), but an exact morphological description has not yet been given. For the commonly used animal model (avian and murine), there are some 3D reconstructions available (Kaufman 1998), but these refer to earlier developmental stages. For the relatively late stages of craniofacial development only 2D outlines (Rossant and Tam 2002) have been given so far.…”
Section: Introductionmentioning
confidence: 99%